Similar adverse outcome rates with high or low oxygen saturation targets in an area with low background mortality - Willgerodt, Nina; Bührer, Christoph; Rossi, Rainer; Kühn, Thomas; Rüdiger, Mario; Avenarius, Stefan; Böttger, Ralf; Olbertz, Dirk M.; Proquitte, Hans; Bittrich, Hans-Jörg; Haase, Roland; Fröhlich, Matthias; et al. (Frontiers in Pediatrics, 2023)
Background Randomized controlled trials have indicated reduced mortality rates in very preterm infants assigned to high, as compared to low oxygen saturation (SpO2) target levels, which is accompanied by higher rates of retinopathy of prematurity and bronchopulmonary dysplasia. The benefit to harm ratio, however, may depend on the local background mortality risk. We therefore aimed to quantitate the riskbenefit ratios of different SpO2 target ranges in 10 tertiary newborn intensive care units (NICU) in East Germany.In a retrospective multicenter study, 1399 infants born between 2008 and 2012 at a gestational age between 24 0/7 and 27 6/7 weeks and with a birthweight below 1250 g were grouped according to the hospital's target SpO2 range (high oxygen saturation group [HOSG] above 90%), low oxygen saturation group [LOSG] below 90%) and the compliance of units with their target SpO2 range. The association between neonatal morbidities, neurodevelopmental outcomes, selected treatment strategies and target SpO2 was calculated using a Chi-square test and Mann-Whitney-U test.Nine of the 10 participating NICUs met their SpO2 target ranges. Five units were considered as HOSG and 5 as LOSG. Necrotizing enterocolitis and intraventricular hemorrhage grade ≥ 2 occurred significantly more frequently in the HOSG as compared to the LOSG (8.4% vs. 5.1%, p 0.02; and 26.6% vs. 17.7%, p<0.001). No significant differences in the mortality rate and the rate of retinopathy of prematurity were found.In our patient population, a lower SpO2 target range was not associated with increased safety risks in extremely preterm infants. We cannot be sure that our outcome differences are associated with differences in oxygen saturations due to the retrospective study design and the discrepancies in site practices.